2014
DOI: 10.1128/aac.02114-13
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Fitness Assays Indicate that the E138A Substitution in HIV-1 Reverse Transcriptase Decreases In Vitro Susceptibility to Emtricitabine

Abstract: We characterized the relative fitness of multiple nonnucleoside reverse transcriptase (RT) inhibitor (NNRTI)-resistant HIV-1 variants in the presence of etravirine (ETV), rilpivirine (RPV), and/or the nucleoside RT inhibitor emtricitabine (FTC) by simultaneous competitive culture and 454 deep sequencing. The E138A substitution, typically associated with decreased virologic responses to ETV-and RPV-containing regimens, confers a clear fitness advantage to the virus in the presence of FTC and decreases FTC susce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
2
4
0
1
Order By: Relevance
“…Conversely, E138Q conferred a 4.3-fold EC 50 increase above WT HIV-1 (2.85 Ϯ 0.08 nM) and no difference from WT RT-SHIV (0.30 Ϯ 0.05 nM). These EC 50 s for WT, E138G, and E138Q HIV-1 were similar to values previously reported (55,57).…”
Section: Rpv La Treatment Of Rt-shiv-infected Macaquessupporting
confidence: 89%
“…Conversely, E138Q conferred a 4.3-fold EC 50 increase above WT HIV-1 (2.85 Ϯ 0.08 nM) and no difference from WT RT-SHIV (0.30 Ϯ 0.05 nM). These EC 50 s for WT, E138G, and E138Q HIV-1 were similar to values previously reported (55,57).…”
Section: Rpv La Treatment Of Rt-shiv-infected Macaquessupporting
confidence: 89%
“…In this study, classic RPV-associated resistance mutations (K101E, E138K, and E138Q) arose at low frequency in a subset of both RPV LA-treated animals and untreated animals. However, these mutations arise from a single base change and confer only 2-to 5-fold resistance to RPV, according to our data and those of others (25,58,60,65,68,79). It is possible that some mutations selected in genomes already encoding Y181V lead to additive levels of resistance, but this is unlikely to have much effect in a virus that already has Ͼ20-fold reduced susceptibility to RPV and that can be transmitted despite high concentrations of drug in tissues and blood.…”
Section: Discussionsupporting
confidence: 71%
“…Recent evidence from the SPREAD program pointed out that E138A (which is included in the IAS‐USA mutation list) is the most frequent NNRTI mutation in naive patients [Hofstra et al, ]. Also, in vitro experiments showed that E138A is most common in HIV‐1 subtype C than B [Sluis‐Cremer et al, ] and that this mutation decreases in vitro susceptibility to 3TC/FTC and RVP [Sluis‐Cremer et al, ].…”
Section: Discussionmentioning
confidence: 99%